Metabolic alterations within the primary visual cortex in blind patients with end-stage glaucoma: a proton magnetic resonance spectroscopy study - Wenqing Zhu; Wenqing Zhu; Wenqing Zhu; Linying Guo; Wenwen Chen; Wenwen Chen; Wenwen Chen; Tingting Liu; Tingting Liu; Tingting Liu; Xinghuai Sun; Xinghuai Sun; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionGlaucoma, a leading cause of irreversible blindness worldwide, imposes a devastating burden on over 11 million end-stage patients through permanent vision loss. Despite this profound disability, the neurochemical basis of preserved cortical plasticity remains unclear, compounded by the challenge of recruiting this vulnerable population for advanced neuroimaging studies.MethodsWe conducted single-voxel proton magnetic resonance spectroscopy (1H-MRS) in 11 blind patients with end-stage primary open-angle glaucoma (POAG) and 11 normal controls to characterize metabolic alterations in the primary visual cortex (V1) and their relationship to residual retinal function.ResultsGlutamate-glutamine complex (Glx), N-acetylaspartate (NAA), choline (Cho), and myo-inositol (Ins) ratios relative to creatine (Cr) were quantified, revealing significantly elevated Glx/Cr in POAG (95% CI: 0.09 ∼ 0.63, P = 0.011), while NAA/Cr, Cho/Cr, and Ins/Cr remained stable (P > 0.05). Notably, the Glx/Cr ratio correlated significantly with the N1-wave latency of mfERG (ρ = -0.676, P = 0.022), independent of other clinical parameters.DiscussionThese findings demonstrate glutamate hyperactivity coexisting with preserved neuronal and osmotic homeostasis in the V1 of end-stage POAG patients, suggesting adaptive neuroglial compensation. The correlation between Glx/Cr ratios and mfERG responses indicates persistent retinocortical signaling despite blindness, highlighting the potential of 1H-MRS as a valuable tool for assessing cortical plasticity in advanced glaucoma rehabilitation.